DESIGN OF A PIPING IRRIGATION SYSTEM ON SUKKARI'S KURMA PLANTATION - Hasyir, Muhammad Humaam Al; Immamuddin, Mohammad (University Muhammadiyah Jakarta, 2023)
Irrigation using pipes is a common thing found in agriculture. In this research, before designing the pipes, a topographic map is first made to find the points on each water exit route in each pipe. Topographic data is obtained from measurement data in the field, then the data is processed in Auto Cad software. After that, the pipe network was designed using Autocad software with 270 tapping exit points with a service level of 100% for an output time of 1 hour. So it is found that the calculation assumption for the average need for plants is 35 liters/day or 0.00000486 m 3 /second/pipe/tree. After obtaining the average results, the pipe needs are planned with a main pipe size of 7 mm, an average distribution pipe of 2.2 mm with a drip hole size of 1.7 mm. Next, the energy loss (Hf) in each pipe was calculated and the result was 0.00000017. The storage uses a capacity of 500 liters with a height of 5 m from the ground, with a value (Hf) of 0.00005398. Pipe planning on date palm plantations can be said to be very helpful to farmers if the design can be implemented and will be more effective.